Colorectal carcinomas containing hypermethylated MLH1 promoter and wild type BRAF/KRAS are enriched for targetable kinase fusions - Cocco, Emiliano (Cancer Res, 2019)
Kinase fusions are rare and poorly characterized in colorectal carcinoma (CRC), yet they present unique opportunities for targeted therapy. In this study, we characterized kinase fusions from patients with advanced CRC who had MSK-IMPACT testing of their tumors between January 2014 and June 2018. Patients were analyzed for the presence of fusions, microsatellite instability (MSI), and RAS/BRAF mutations. Mismatch repair (MMR) immunohistochemistry (IHC) and promoter hypermethylation status of MLH1 (MLH1ph) in MSI-H CRC with fusions were investigated. Fusion transcripts were confirmed using a targeted RNAseq panel assay. Of 2314 CRCs with MSK-IMPACT testing, 21 harbored kinase fusions. Overall 57% (12/21) of CRC fusions were MSI-H/MMR-D. Loss of MLH1 and MLH1ph was confirmed in all 12 and all 10 cases with available material, respectively. Fusions were present in 5% of MSI-H/MMR-D CRC compared to 0.4% of MSS/MMR-P CRC (p<0.001), and 15% of MSI-H/MMR-D CRC with wild type RAS/BRAF. Of 24 total MLH1-deficient CRC with MLH1ph and wild type RAS/BRAF, 10 (42%) harbored kinase fusions. Kinase fusions in MSI-H CRC were associated with sporadic MLH1ph rather than with Lynch syndrome, and these patients may be eligible for kinase inhibitors, particularly following resistance or toxicity in response to immunotherapy. These findings identify a molecular subset of CRC with kinase fusions that may be responsive to kinase inhibitors.